(untitled) (UUM Journal of Legal Studies, 2025)
A pregnancy can be terminated because of the problem of foetal anomaly. However, parents may lose the right to terminate the pregnancy if there is negligence in prenatal diagnosis. Such negligence may consequently result in the mother giving birth to a disabled child. This article examines whether women in Malaysia have the legal right over a wrongful birth claim should there be negligence by the doctors who carried out the prenatal diagnosis. This article employs the doctrinal comparative method. First, this article reviews the relevant literature on the topic of women’s right to terminate a fetus with abnormalities and the legal status of the foetus. Next, the article will analyse the Utilitarian theory and the Principle of Reproductive Autonomy, which the authors claim will provide the fundamental argument for women to have the right to abort a pregnancy with foetal anomaly. A negligent prenatal diagnosis that results in the woman delivering a disabled baby undermines a woman’s right to reproductive autonomy, her right to make an informed consent for a legal abortion. Following that, an acknowledgment of the woman’s right to reproductive autonomy and the right to initiate a wrongful birth claim is demonstrated by highlighting and discussing several international court cases. The analysis of comparison is the final part, in which the authors present the possibility of women in Malaysia claiming a wrongful birth claim should there be negligence in the prenatal diagnosis by medical practitioners. In conclusion, the authors have made the case that women in Malaysia have the right to legally abort a pregnancy with foetal anomaly and could sue for wrongful birth if a prenatal diagnosis was made negligently. However, it might be challenging to prove the claim given the ambiguity of Malaysia’s abortion legislation. This article has made an important contribution to the current literature as it has discussed the potential rights of women in Malaysia to file a lawsuit over a wrongful birth claim should there be negligence in the prenatal diagnosis by medical practitioners.